2008
DOI: 10.1002/elan.200804219
|View full text |Cite
|
Sign up to set email alerts
|

Novel Studies about the Electrooxidation of a Deoxynivalenol (DON) Mycotoxin Reduction Product Adsorbed on Glassy Carbon and Carbon Paste Electrodes

Abstract: A novel and fast square-wave adsorptive anodic stripping voltammetric procedure on glassy carbon and carbon paste electrodes is described for the indirect trace quantitation of deoxynivalenol (DON) mycotoxin that frequently contaminates soya and foodstuff. The in situ homogeneous reduction of the toxin by product/s of dissolved oxygen electroreduction in pH 8 buffer solution makes the quantitation of DON possible through a simple electroanalytical technique. Moreover, its potential use for the analysis of real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As a result, many studies have been reported, which use these electrodes in different EC systems (e.g. electroanalysis, biosensing, and electro‐catalysis). To the best of our knowledge, no studies have reported the use of EC techniques in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many studies have been reported, which use these electrodes in different EC systems (e.g. electroanalysis, biosensing, and electro‐catalysis). To the best of our knowledge, no studies have reported the use of EC techniques in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical methods reported for the determination of DON include PCR, GC, GC-MS, HPLC, thin-layer chromatography and enzyme-linked immunosorbent assay (ELISA) [ 10 16 ]. Some of these methods allow good accuracy of quantification and good detection limits, but they are not cost effective; some suffer from low selectivity and usually require significant amounts of time associated with labour-intensive sample cleanup, sophisticated instrumentation, skilled operators or technical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained LOD for DON is similar or better than those published for a stripping adsorptive square‐wave voltammetric method on glassy carbon (41 μg L −1 , 1.4×10 −7 mol L −1 ) or carbon paste (3.6 μg L −1 , 1.2×10 −8 mol L −1 ) electrodes and polarographic methods (8.6 μg L −1 , 2.9×10 −8 mol L −1 ) . The reported LOD values for DON determination methods based on hydrolysis procedures prior to the electrochemical measurement, by square‐wave voltammetry (2.7 mg L −1 , 9.1×10 −6 mol L −1 ) or differential pulse voltammetry using 96‐well screen‐printed microplates (1.1 mg L −1 , 3.7×10 −6 mol L −1 ) , are worse than the LOD value for the method proposed in the present paper.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, regardless the characteristics of the techniques and methods employed, extraction and clean‐up steps are usually required. For this reason, more or less laborious clean‐up methods are employed in all published electroanalytical methods for DON determination in real samples. We have explored the applicability of the developed method for the determination of DON in rice samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation